Raising Native Cattle in Thailand: Status, Problems, Needs and the Development of a Model - Umpapol, H.; Songwicha, C.; Jitrajak, T.; Patkit, A.; Sripandon, J. (Pakistan Journal of Nutrition, 2019)
Background and Objective: This study was designed to investigate the status and problems with raising Thai native cattle, as well as farmers’ needs and developed a model to address these issues using a mixed research approach combining qualitative and quantitative research. Materials and Methods: The procedures included document reviews and focus group interviews in the form of participatory rural appraisals for a strengths, weaknesses, opportunities and threats (SWOT) analysis. In-depth and multilateral interviews were performed with 90 farmers of Thai native cattle. A model of methods was employed for raising Thai native (TN) cattle developed through participatory action research (PAR). A stratified random sampling technique was used across a study population of 40 groups of TN cattle farmers who were members of the Sakon Nakhon Provincial Livestock Office. The instruments used in this study included a measurement of training achievement, a test for satisfaction and a training evaluation form. Results: The problems faced by the farmers who raised Thai native cattle included a lack of shared knowledge about raising quality TN cattle, common problems in raising the cattle and housing management practices that are inconsistent with the cattle's reproductive states. Additional challenges include selecting local feed to be mixed with feed concentrates and hygienic management to avoid major diseases or parasites. The farmers need to gain additional knowledge and experience and to share technologies for raising quality TN cattle. This includes determining appropriate practices for managing housing and producing a feed formula for TN cattle that uses inexpensive, locally available feeds. The model for raising TN cattle included a training session intended to develop better management practices and to help farmers produce better animals. Conclusion: The training session demonstrated improvements in farmers' knowledge, the results of the training were positive and the farmers’ satisfaction with the workshop was high.